Doxycycline‐loaded carboxymethyl cellulose/sodium alginate/gelatin hydrogel: An approach for enhancing pressure ulcer healing in a rat model - Aldaghi, Niloofar; Kamalabadi‐Farahani, Mohammad; Alizadeh, Morteza; Salehi, Majid (Journal of biomedical materials research. Part A, 2024)
Pressure ulcers, or bedsores, are created by areas of the skin under prolonged pressure and can lead to skin and underlying tissue damage. The present study evaluated the effects of carboxymethyl cellulose/sodium alginate/gelatin (CMC/Alg/Gel) hydrogel containing doxycycline (DOX) on improving the healing process of pressure ulcers. The magnet was used to apply pressure on the dorsum skin rat to induce a pressure ulcer model. Then sterile gauze, CMC/Alg/Gel, and CMC/Alg/Gel/1% w/v DOX hydrogels were used to cover the wounds. Blood compatibility, weight loss, cytocompatibility, drug release rate, cell viability, wound closure, and re‐epithelialization were evaluated in all animals on the 14th day after treatment. In vivo results and histopathological evaluation showed 56.66% wound closure and the highest re‐epithelialization in the CMC/Alg/Gel/1% w/v DOX hydrogel group (14 days after treatment). Furthermore, real‐time PCR results indicated that the hydrogel containing DOX significantly decreased the expression of the MMP family consisting of MMP2 and MMP9 mRNA and also increased the expression of vascular endothelial growth factor VEGF mRNA. This study suggested that the addition of DOX, an antibiotic and MMP inhibitor, to hydrogels may be effective in the healing process of pressure ulcers.